Expression and correlation of endoglin, sEndoglin, and MMP-14 on preeclampsia placenta - Febriana Catur Iswanti; Ninik Mudjihartini; Reni Paramita; Yuditiya Purwosunu; Ani Retno Prijanti (Indonesian Society for Biochemistry and Molecular Biology, 2024)
Background: Hypertensive disorders, particularly preeclampsia, are major contributors to maternal mortality and neonatal morbidity. Angiogenic imbalance plays a critical role in placental ischemia, a hallmark of preeclampsia. Purpose: This study aimed to investigate the roles of endoglin, soluble endoglin (sEndoglin), and matrix metalloproteinase-14 (MMP-14) in the angiogenic imbalance observed in preeclampsia placentas compared to normal-term placentas. Method: A cross-sectional study was conducted using 68 placental samples: 34 from normal-term pregnancies and 34 from preeclampsia cases. Concentrations of endoglin, sEndoglin, and MMP-14 were measured using the sandwich ELISA method, and protein levels were determined using the Christian Warburg method. Data were analyzed using SPSS version 20. Results: The concentration of endoglin in preeclampsia placentas was slightly higher (1.37 [0.2–2.2] ng/μg protein) compared to normal placentas (1.12 [0.6–14.1] ng/μg protein), although the difference was not statistically significant. In contrast, sEndoglin (0.05 [0.0–0.01] ng/μg protein vs. 0.02 [0.0–0.3] ng/μg protein) and MMP-14 (0.14 [0.1–0.6] ng/μg protein vs. 0.11 [0.1–1.3] ng/μg protein) concentrations were significantly higher in preeclampsia placentas compared to normal placentas. All parameters showed a gradual decrease with advancing gestational age. sEndoglin and MMP-14 demonstrated a strong positive correlation (r = 0.658, p < 0.001), while endoglin and MMP-14 exhibited a moderate positive correlation (r = 0.554, p < 0.001). Conclusion: Endoglin, sEndoglin, and MMP-14 were differentially expressed in preeclampsia placentas, with sEndoglin and MMP-14 significantly elevated. These findings highlight their potential role in angiogenic imbalance and may provide insight into the pathophysiology of preeclampsia.